Distal myopathy with cachexia: an unrecognised phenotype caused by dominantly-inherited mitochondrial polymerase γ mutations. Issue 1 (29th August 2012) - Pitceathly, Robert D S; Tomlinson, Susan E; Hargreaves, Iain; Bhardwaj, Nisha; Holton, Janice L; Morrow, Jasper M; Evans, Julie; Smith, Conrad; Fratter, Carl; Woodward, Cathy E; Sweeney, Mary G; Rahman, Shamima; et al.
Abstract : Background: The myopathy associated with mutations in the nuclear-encoded mitochondrial DNA maintenance gene POLG, coding for the catalytic subunit of DNA polymerase, is typically proximal with early ophthalmoplegia. Results: We report two unrelated patients in whom a distal, mainly upper limb, myopathy was the predominant and early clinical feature. One patient also suffered with marked cachexia. DNA genomic sequence analysis identified novel dominant heterozygous missense POLG mutations (Leu896Arg and Tyr951His) located within the conserved catalytic polymerase domain of the protein in both cases. Conclusions: Distal upper limb myopathy/cachexia is not previously described with dominant POLG mutations and our observations further highlight the diverse clinical spectrum of POLG -related mitochondrial disorders. These data indicate that dominant POLG mutations should be considered in the differential diagnosis of distal upper limb predominant myopathy.